2022
DOI: 10.1101/2022.04.30.490097
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hypoxia-mediated regulation of DDX5 through decreased chromatin accessibility and post-translational targeting restricts R-loop accumulation

Abstract: Local hypoxia (low oxygen) occurs in most solid tumors and is associated with aggressive disease and therapy resistance. Widespread changes in gene expression play a critical role in the biological response to hypoxia. However, most of the prior research has focused on hypoxia-inducible genes in hypoxia as opposed to those which are decreased. Using ATACseq, we demonstrate that chromatin accessibility is decreased in an oxygen-dependent manner, predominantly at gene promoters and specific pathways are impacted… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 73 publications
(112 reference statements)
0
1
1
Order By: Relevance
“…A recent study showed that DDX5 expression levels were reduced under hypoxic conditions in various cancer cell lines, including RKO and HCT116, and so on (Leszczynska et al, 2023). However, under our experimental setup and hypoxic conditions, we observed no apparent change in the expression levels of DDX5.…”
Section: Discussioncontrasting
confidence: 73%
“…A recent study showed that DDX5 expression levels were reduced under hypoxic conditions in various cancer cell lines, including RKO and HCT116, and so on (Leszczynska et al, 2023). However, under our experimental setup and hypoxic conditions, we observed no apparent change in the expression levels of DDX5.…”
Section: Discussioncontrasting
confidence: 73%
“…Further evidence showed depletion of DDX5 reduced growth and mitochondrial dysfunction in chemoresistant SCLC (small cell lung cancer) cell line by possibility of reduction of intracellular succinate which serves as direct electron donor to mitochondrial (Xing et al 2020). DDX5 reduced expression in various cancer cell lines and tumor xenografts under hypoxia condition and rescued DDX5 in hypoxia showed R-loop levels accumulation further (Leszczynska et al 2023). The resolution activation of DDX5 on R-loop in cell was reported only years ago and several co-regulators were also focused in recently as introduced in this text.…”
Section: Discussionmentioning
confidence: 78%